Prescription audit of patients in a teritiary care hospital - Marupaka, Janardhan; Kodam, Laxmipathi; Tamma, Naveen Kumar; Karedla, Srinivasu (International Journal of Basic & Clinical Pharmacology, 2020)
Background: This study was prescribed errors to promote irrational use of drug and decrease patience compliance. Prescription audit can improve prescribing practices and patients to receive high quality drugs. Methods: The study was observational carried out in 150 patients attending outpatient department for period of 6 months from April 2019 to October 2019. Data was analysed using WHO core indicators Results: 16% of prescriptions demographic details like age, sex, age were incomplete. In few (15%) prescriptions omission of diagnosis and irrational combination was reported. Dosing errors like doses and duration of treatment were not mentioned in some of prescriptions. Percentage of antibiotics per prescription was found to be 23.64%, which is much higher than the ideal value recommended by WHO. Conclusions: The average number of drugs was higher in prescriptions and trend of polypharmacy was noted with antibiotics usage. Dosing error and few prescriptions were irrational FDCs. Generic drugs were written in majority of prescriptions from essential drug list. Our study need to highlight to write rational prescription by adhering to WHO guidelines with feed back to prescribers and training session regarding safe use of drugs.